How attitudes towards vaccination change in the face of an outbreak. Issue 3 (4th March 2021) - Talarek, Ewa; Chazan, Magdalena; Winiarska, Paulina; Dembiński, Łukasz; Sobierajski, Tomasz; Banaszkiewicz, Aleksandra
ABSTRACT: Outbreaks of infectious diseases cause great fear and a desire to avoid infection. One of the most effective outbreak containment methods is vaccination. However, in order for this strategy to be effective, a majority of the susceptible population should be vaccinated in a short time. This may require changing the practice of immunization execution and changing attitudes toward vaccination. In the survey on the attitudes of Polish parents and guardians toward vaccinations, we asked about the acceptance of vaccination in places other than health-care facilities in both non-epidemic and epidemic conditions. The study was conducted using an anonymous questionnaire in two Warsaw hospitals between August 2018 and February 2019 and was addressed to parents and legal guardians of children. At the time of the survey, "epidemic" was a hypothetical term. Two hundred fifty respondents participated in the study. The pharmacy was the most accepted non-healthcare facility vaccination location, both normally and during an outbreak, with 54.4% (123/226) and 75.2% (170/226) of respondents finding pharmacies an acceptable location, respectively. A gas station had the lowest acceptance: 5.8% (13/226) and 28.8% (65/226), respectively. The only statistically significant demographic factors affecting acceptance of each vaccination location were male sex ( p = .001) and higher education level ( p = .001). Of those surveyed, 58.5% (131/224) would approve of vaccination in front of a hospital or outpatient clinic during an outbreak; 70.5% (43/61) of men versus 54.0% (88/163) of women, p = .026. In conclusion, during an outbreak, people would be more likely to accept vaccination at locations other than a health-care facility.